Biochemical and Organoleptic Characterization of Tamarillo Wine as Alternative Base Material for Alcoholic Beverage Production - Bao, Antonia P.; Limbu, Umbu N.; So'o, Fransiska (Jurnal Biologi Tropis, 2024)
The Tamarillo fruit, commonly known as the Dutch Eggplant (Solanum betaceum), is one of the tropical fruits that thrives in the Bajawa region of Ngada Regency. However, the fruit is still consumed directly or without further processing into food or beverage products.  A study aimed at determining the effect of the concentration of tamarillo fruit on the biochemical and organoleptic characteristics of tamarillo wine. The biochemical characteristics to be measured include ethanol content, reducing sugar content, total acidity, pH, antioxidant content, as well as the number of live and dead yeast. Meanwhile, organoleptic aspects include color, clarity, aroma, taste, and the preferences of the panelists. The research method used is a completely randomized design with 3 treatments, namely the concentration of Dutch eggplant fruit: water ratios of 1:1, 1:2, and 1:3, with 3 replications for each treatment. The research results show that the wine made from starfruit with a concentration treatment of 1:3 has the highest biochemical characterization results, including ethanol content, total acidity, pH, antioxidants, viable yeast count, and dead yeast count, compared to the concentrations of 1:1 and 1:2. However, it has the lowest reducing sugar content. The organoleptic test shows that the wine with a treatment concentration of 1:3 has the highest scores for color, clarity, aroma, taste, and preference because it has a red color, clarity, fruity and alcoholic aroma, fruity and alcoholic taste, and is favored by the panelists.